Hedonic Shopping Value Dan Shopping Lifestyle Terhadap Impulse Buying Dengan Positive Emotion Sebagai Variabel Intervening Pada Marketplace Shopee - Sindi Mei; Muhammad Sulton; Didik Puji Wahyono; Muhammad David (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Indonesia has a large amount of internet penetration, one of the positive impacts of the development of technology and information is the development of the world of business and marketing. One of the most striking phenomena in the field of business and marketing in this digital era is the emergence of e-commerce, the number of e-commerce users in Indonesia will reach 178.94 million people in 2022. The aim of this research is to explore the influence of hedonic and lifestyle shopping on impulse buying. This research method uses a quantitative descriptive research type, there are intervening variables whose influence can be tested using the path analysis method. The findings from this research are that hedonic shopping value and shopping lifestyle have a positive and significant influence on impulse buying